Wisata Konvensi : Potensi Gede Bisnis Besar - Tri Nugroho (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2014)
MICE (Meeting, Incentive, Conference, Exhibition) in this time still represent the potential market of tourism in Yogyakarta. At the moment more‘s a lot of activity of MICE performed in Yogyakarta, is so that expected in a period to coming to Yogyakarta become the target of MICE after Bali. With the existence of the growing tourism MICE, hence hotel in Yogyakarta of both for have there is and also which in the process of out for development make the meeting room (Ballroom) which can accommodate until 2.500 visitors. Some hotelss are ready to for example Prodigal of Ambarruko Hotel, Sahid Rich Hotel, propose the readily Tentrem Hotel becoming Yogyakarta as the town of target MICE, with the goal of 65% activity MICE and 35% guests from Travel Agent (Kompas com. 28 June 2014).